Jawabanmu

2015-07-21T07:11:27+07:00
1. x → 0 √ 1 + 2x  −  √ 1 − 2x
     x
    

Pembahasan :
Untuk mempermudah penulisan, misalkan :
√ 1 + 2x  −  √ 1 − 2x = f(x)
     x
    

Dengan metode perkalian sekawan :
lim
x → 0
f(x) = lim
x → 0
√1 + 2x − √1 − 2x . √1 + 2x + √1 − 2x
             x √2x + 1 + √1 − 2x
lim
x → 0
f(x) = lim
x → 0
  (1 + 2x) − (1 − 2x)
x (√1 + 2x + √1 − 2x)
lim
x → 0
f(x) = lim
x → 0
              4x
x (√1 + 2x + √1 − 2x)
lim
x → 0
f(x) = lim
x → 0
             4
√1 + 2x + √1 − 2x
lim
x → 0
f(x) =                 4
√1 + 2(0) + √1 − 2(0)
lim
x → 0
f(x) =       4
√1 + √1
lim
x → 0
f(x) = 4
2
lim
x → 0
f(x) = 2


2. x → 4 √ 2x + 1  −  √ x + 5           4 − x
Pembahasan :
Untuk mempermudah penulisan, misalkan :
√ 2x + 1  −  √ x + 5 = f(x)            4 − x
Dengan metode perkalian sekawan :
lim
x → 4
f(x) = lim
x → 4
√2x + 1 − √x + 5 . √2x + 1 + √x + 5
             4 − x √2x + 1 + √x + 5
lim
x → 4
f(x) = lim
x → 4
     (2x + 1) − (x + 5)
(4 − x) (√2x + 1 + √x + 5)
lim
x → 4
f(x) = lim
x → 4
                -(4 − x)
(4 − x) (√2x + 1 + √x + 5)
lim
x → 4
f(x) = lim
x → 4
            -1
√2x + 1 + √x + 5
lim
x → 4
f(x) =                -1
√2(4) + 1 + √4 + 5
lim
x → 4
f(x) =      -1
√9 + √9
lim
x → 4
f(x) = -1
 6

1 5 1